Djava Dvipa Boardgame - Nugroho, Listyanto Aji (Indonesian Journal of History Education, 2024)
The objective of this study is to create a gamified history learning tool that delves into students' comprehension of the grand kingdoms of the Nusantara, sparks their interest in learning, and encourages exploration of the cultural heritage of the Nusantara. The research employed the ADDIE development model as its methodology. The outcome of this investigation is the "Djava Dvipa," a thoughtfully crafted educational board game incorporating elements of the snake and ladder game. Hypothesis testing results indicate the effectiveness of the Djava Dvipa board game in enhancing the understanding of Nusantara's historical insight. The paired sample t-test analysis yielded a significance value (sig) of 0.000, which is below 0.05, signifying the acceptance of the alternative hypothesis (H1) and the rejection of the null hypothesis (H0). This study underscores the substantial contribution of the gamification approach, embodied in Djava Dvipa, towards elevating the Nusantara insight among students. The board game presents an intriguing alternative for history instruction that holds promise for integration into the landscape of history education in Indonesia.